Waste People and the Vampiric Society: The Heterotopia of Migrant Workers in Chen Qiufan's Waste Tide. Issue 3 (1st December 2021) - Guangzhao, Lyu
Abstract : Chen Qiufan's 2013 novel Waste Tide has become one of the most popular stories in Chinese New Wave Science Fiction, especially after the publication of its English version in 2019. This essay argues that in addition to the environmental concerns Waste Tide brings to the fore, the novel also calls for a discussion centered on migrant workers in China. Rendered as waste people on Silicon Isle, these migrant workers find themselves trapped in the duality of "economic acceptance" and "social rejection, " forming an autonomous community that can be read through Michel Foucault's notion of heterotopia. Out of the humiliation imposed by the Silicon Isle natives and the resulting mentality of failure and trauma, the waste people have developed a desire for change and transgression. However, their efforts and sacrifice for self-liberation turn out to be in vain, because in doing so, they are consumed by the vampiric logic of market competition. Such a competition, in fact, is evident not only in the fictional Silicon Isle, but also in the real cities benefitting from China's market-oriented transition.